Prospects for Massive Development of Koperasi Desa Merah Putih to Accelerate the Achievement of SDGs - Eko Wijayanto; Eny Haryati; Dian Ferriswara (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the strategic role of Koperasi Desa Merah Putih (Red and White Village Cooperative) in accelerating the achievement of the Sustainable Development Goals (SDGs) in Indonesia, using qualitative document analysis as the primary method. Key institutional documents—namely the Articles of Association/Bylaws (AD/ART) and the Village Medium-Term Development Plan (RPJMDes)—were analyzed to identify cooperative values, integration into local development planning, and contributions to specific SDG indicators. Findings reveal that the cooperative’s core principles—voluntary membership, inclusivity, democratic governance, and equitable profit sharing—align strongly with SDG 1 (No Poverty), SDG 5 (Gender Equality), and SDG 8 (Decent Work and Economic Growth). The RPJMDes analysis indicates formal recognition of the cooperative as a driver of economic empowerment, gender equity, and sustainable community development, with potential scalability to other villages and rural areas in Indonesia. Further analysis demonstrates how the cooperative actively promotes women’s participation in leadership roles, supports income-generating activities for marginalized groups, and encourages the localization of economic value chains. These practices foster not only economic inclusion but also enhance community resilience and social cohesion. However, several challenges were identified. These include inconsistent documentation quality, lack of standardized performance metrics, and limited results-based evaluation frameworks that hinder a thorough impact assessment. Additionally, there remains a gap in digitalization, which affects data transparency and accessibility. The study’s novelty lies in its document-based approach, offering a replicable model for assessing SDG readiness in similar rural institutions. Unlike interview-based studies, this method reduces subjective bias and highlights the importance of formal governance structures.